Skywalks : Robert Gordon's untold story of Hallmark's Kansas City disaster - Paul, R. Eli, 1954- (University of Nebraska Press, 2023)
"The subject of R. Eli Paul's study is the 1981 Hyatt Regency Kansas City hotel disaster in which 114 people were killed. The story is told through the actions of Kansas City attorney Robert Gordon, an insider to the investigation and litigation of the "Federal Skywalk Cases.""--